Implications of the 1976 Arab-Israeli military status - Pranger, Robert J.; Tahtinen, Dale R. (Washington : American Enterprise Institute for Public Policy Research, 1976)
The book discusses where and how the weapons in the hands of the warring states are likely to be used if there is another outbreak of hostilities.
Includes bibliographical references.
ahz 12/03/2019
Loans
Keywords: Arab-Israeli conflict; Arab countries; Israel